1985
DOI: 10.1007/bf00024230
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural responses and tolerance of freshwater benthic cyclopoid copepods to hypoxia and anoxia

Abstract: The response of four benthic cyclopoid copepods, Acanthocyclops viridis (Megacyclops viridis) (Jurine, 1820), Macrocyclops albidus (Jurine), Eucyclops agilis (Koch, Sars) (Eucyclops serrulatus) (Fischer, 185 1) and Paracyclopsfirnbriatus (Fischer), to hypoxia and anoxia was investigated. All of these species died within six hours when confronted by totally anoxic conditions, but all survived four days at oxygen saturation levels as low as 25%. Males succumbed to the effects of anoxia more rapidly than the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Male C. confluens were less resistant than egg sac bearing and non-gravid females. A similar sex-specific response has been shown by Tinson & Laybourn-Parry (1985). The authors found female cyclopoid copepods to be more tolerant of anoxia than males.…”
Section: Discussionsupporting
confidence: 73%
“…Male C. confluens were less resistant than egg sac bearing and non-gravid females. A similar sex-specific response has been shown by Tinson & Laybourn-Parry (1985). The authors found female cyclopoid copepods to be more tolerant of anoxia than males.…”
Section: Discussionsupporting
confidence: 73%
“…Low concentrations of edible phytoplankton may preclude vertical migration. Many epiphytic and benthic microcrustaceans also exhibit strong vertical movements with declining oxygen concentrations (Meyers 1980;Tinson and Laybourn-Parry 1985). In a study of horizontal migration,…”
mentioning
confidence: 99%
“…Hanazato and Yasuno (1989) and Lampert et al (2010) suggested that Daphnia adults, which often overwinter, can build their populations faster than smaller zooplankton forms, which possibly happened in the case of the studied forest ponds. Additionally, the occurrence of some littoral species, such as e.g., M. viridis which is known to be well adapted for living in ponds characterized by rich organic matter and oxygen deficiencies, proves these arguments (Tinson and Laybourn-Parry, 1985;Rybak and Błędzki, 2010). In the forest ponds, a high concentration of ammonium was also observed, which is likely to have come from leaf decomposition in anaerobic conditions.…”
Section: Discussionmentioning
confidence: 92%